2021
DOI: 10.1097/md.0000000000027712
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte ratio is associated with tumor localization and outcomes in metastatic colorectal cancer

Abstract: The aim of this study was to investigate the predictive and prognostic value of PLR, and the relationship between PLR and tumor localization.A total of 229 patients with de-novo metastatic CRC were retrospectively analyzed. The cutoff value for PLR was defined by the receiver operating characteristic (ROC) curve analysis and threshold value of 196.5 as best cut-off value was found.The higher rate of BRAF mutation was significantly detected for patients with PLRhigh (> 196.5) compared to those with PLRlow (≤196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…As mentioned earlier, combining liquid biopsy sources for cancer detection and localization is effective. In patients with metastatic colorectal cancer and upper urinary tract cancer with a tumor diameter >3 cm, the platelet/lymphocyte ratio was found to be correlated with tumor location and prognosis (106,107). In patients with oral and lingual squamous cell carcinoma, the platelet-to-neutrophil ratio can predict lymph node metastasis (108).…”
Section: Emerging Technologies For Tumoreducated Platelets Biomarkersmentioning
confidence: 98%
“…As mentioned earlier, combining liquid biopsy sources for cancer detection and localization is effective. In patients with metastatic colorectal cancer and upper urinary tract cancer with a tumor diameter >3 cm, the platelet/lymphocyte ratio was found to be correlated with tumor location and prognosis (106,107). In patients with oral and lingual squamous cell carcinoma, the platelet-to-neutrophil ratio can predict lymph node metastasis (108).…”
Section: Emerging Technologies For Tumoreducated Platelets Biomarkersmentioning
confidence: 98%
“…OS and DFS were significantly better in patients with low PLR compared to patients with high PLR. 87 In a large-scale retrospective study of 1868 patients with CRC, Kim et al 39 demonstrated a PLR AUC of 0.556, with a mean PLR of 200.17 ± 168.96 and a cut-off of 160. Interestingly, the prognosis based on NLR and PLR differed depending on the stage of the cancer.…”
Section: Platelet-to-lymphocyte-ratio (Plr)mentioning
confidence: 99%
“…Increased PLT in patients with CRC is associated with poor prognosis and an increased risk of distant metastasis. 87 Thrombocytosis is related with systemic inflammation due to cancer, additionally, thrombosis can show systemic inflammatory and tumor activity. However, the assessment of the diagnostic power of PLR did not show that it is an indicator of high diagnostic utility in colorectal neoplasms.…”
Section: Inflammation-related Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations